DIFFERENCES IN ATTITUDES TOWARD PRE-MARITAL ABORTION IN TEENS ATTENDING HIGH SCHOOL AND MA - Ady Waskito (Sean Institute, 2021)
School is a secondary education environment. For children who have attended school, the environment that every day he entered in addition to the home environment is the school. Teenagers who have been sitting in junior high school or high school generally spend about seven hours a day in school. This means that almost a third of his time each day is spent in school. It is not surprising that the influence of school on the development of adolescent mental health is quite large. As an educational institution, which is the case with the family, the school also teaches the values and norms that apply in society. The problem of sex in adolescents often concerns parents, as well as educators, government officials, experts, and the public. Having casual sex before marriage will eventually carry risks, such as pregnancy. An unwanted pregnancy, because it is not in accordance with the demands and norms that apply in society, results in abortion as a way that is considered to solve their problems. The study aims to find out how attitudes toward pre-marital abortion differ in teens attending high school and MA. The approach used is a quantitative approach with comparative research methods. The research was conducted at Dharma Karya UT High School, Pamulang and MA Manaratul Islam, Jakarta with a sample number of 50 people, 25 high school students and 25 MA students, which were taken by random sampling technique. The data collection instrument used is the Likert model scale. Data processing and analysis techniques are performed with statistical analysis that includes Pearson's Product Moment correlation to test item validity, Alpha Cronbach to test the reliability of data collection instruments, and T-test for testing research hypotheses. The number of valid items for the attitude scale towards pre-marital abortion is 40 items. The reliability of the attitude scale towards pre-marital sex was 0.8366. Based on the T-test, the result of t-calculate (0.989) < t-table (2,021). There was no significant difference in pre-marital abortion attitudes between high school and MA. The results showed that there was no difference in attitudes towards pre-marital abortion in adolescents who attended high school and MA. This is evident from the categorization, both high school students and MA students as much as (40%) have a fairly negative attitude towards pre-marital abortion. It is recommended for further researchers to create pre-marital abortion items in the context of adolescents, in order to represent the research sample. Then it needs to be traced further, what factors can shape a teenager's positive attitude towards pre-marital abortion. So that this can be used as a preventive measure in preventing increasing moral degradation among adolescents, especially Indonesian students, related to pre-marital abortion.